Comparative Effectiveness of Abiraterone and Enzalutamide in Patients With Metastatic Castration-Resistant Prostate Cancer in Taiwan - Li, Pei-Yu; Lu, Ying-Hao; Chen, Chung-Yu (Frontiers in Oncology, 2022)
Background: Abiraterone and enzalutamide are widely used as first-line treatment for metastatic castration-resistant prostate cancer (mCRPC); however, their efficacy in mCRPC has been inconsistently demonstrated in other outcome studies from real-world databases. The aim of our study was to assess the comparative effectiveness of abiraterone and enzalutamide in patients with mCRPC using real-world data from Taiwan. Methods: This retrospective cohort population-based study included patients identified in the Taiwan National Health Insurance Research Database who had been diagnosed with mCRPC and who had taken abiraterone or enzalutamide between December 2014 and August 2017. The study’s outcome evaluated the differences in overall survival (OS) and time to treatment failure (TTF) between abiraterone and enzalutamide over a 15-month follow-up period. The patients were followed from the index date to when the outcome occurred, to December 31, 2018, or to the patients’ withdrawal from the National Health Insurance program. The estimated relative treatment effects of abiraterone and enzalutamide on OS and TTF were adjusted by the inverse probability of treatment weighting (IPTW) using the Kaplan–Meier method and a Cox proportional hazards model. Results: The abiraterone and enzalutamide groups consisted of 1046 and 118 patients, respectively. After IPTW adjustment, 1164 patients in the abiraterone group and 1158 in the enzalutamide group underwent an outcome evaluation. Enzalutamide showed a similar OS rate to that of abiraterone (57.58% vs. 49.51%, p = 0.095 by log-rank test). Enzalutamide significantly reduced the risk of death for mCRPC when compared with abiraterone (adjusted hazard ratio [aHR], 0.828; 95% CI 0.791–0.938). However, similar results were not observed in the TTF outcomes (63.84% vs. 67.79%, p = 0.2651 by log-rank test; aHR, 0.902; 95% CI 0.812–1.002). Conclusion: In conclusion, enzalutamide was associated with better OS for mCRPC than abiraterone in the Taiwan population. Our study showed that there was no statistically significant difference in TTF between enzalutamide and abiraterone. Studies with longer surveillance of enzalutamide and abiraterone using real-world databases are needed.